Accounting Marketing by Accounting Offices in the State of Sao Paulo - Peleias, Ivam Ricardo; Hernandes, Danieli Cristina Ramos; Garcia, Mauro Neves; Silva, Dirceu da (Review of Business Management, 2007)
This article presents a portion of the result of a research carried through between the last quarter of 2004 and the first quarter of 2005, to identify as 259 accounting services offices in the State of Sao Paulo use or not the Marketing tools. The study executed combined empirical research to identify excellent aspects about the reality of the offices, bibliographical revision, and field research, in its first stage by means of a depth interview with the partners of five offices, and later with the use of a questionnaire with 49 assertive, answered by the partners of the 259 accounting offices. The revision of literature disclosed international experiences in the use of the Marketing that can contribute the offices have one better image for its customers, and for the development of its businesses. The data collected with the questionnaires have been treated by the Descriptive Statistics and analyzed by the use of Mean, because the collected data was not adherent to the normal curve. The achieved results have disclosed that the use of the Marketing tools is intuitive and embryonic in the sector. The research supplies information that will serve of subsidy so that the accounting entrepreneurs adopt the Marketing tools as an alternative for bigger valuation of its services for the market, and an element of support to its business. Key-words: Marketing. Services marketing. Accounting marketing. Accounting services offices. Services. Accounting.